The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3390/cancers12092410
|View full text |Cite
|
Sign up to set email alerts
|

A Distinctive microRNA (miRNA) Signature in the Blood of Colorectal Cancer (CRC) Patients at Surgery

Abstract: Background: Liquid biopsy (LB) provides an examination of the peripheral blood of cancer patients for circulating tumor cells, cell-free nucleic acids and microRNAs (miRNAs) and is an established tool of precision medicine. Unlike most previous LB studies that focused on advanced metastatic colorectal cancer (CRC), we assessed miRNA dysregulation in blood samples obtained on the day of surgery from patients with primary CRC lesions but no clinical evidence of extra-colonic diffusion. In this study, plasma prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 69 publications
2
23
0
Order By: Relevance
“…A number of studies have recently manifested the association of miR-222-3p dysregulation with cancer initiation and progression (29)(30)(31). Despite recent developments in cancer diagnosis and treatment, there are still numerous problems associated with the pathogenesis of cancer progression, disease recurrence and drug resistance.…”
Section: Emerging Roles and Mechanisms Of Microrna-222-3p In Human Camentioning
confidence: 99%
“…A number of studies have recently manifested the association of miR-222-3p dysregulation with cancer initiation and progression (29)(30)(31). Despite recent developments in cancer diagnosis and treatment, there are still numerous problems associated with the pathogenesis of cancer progression, disease recurrence and drug resistance.…”
Section: Emerging Roles and Mechanisms Of Microrna-222-3p In Human Camentioning
confidence: 99%
“…The newest findings have shown that miRNAs play an important role in many signal pathways. Dysregulated expression of several miRNA expressions is associated with a higher malignant potential and poor clinical response to therapy, and analysis of specific miRNA expression patterns can be used to predict chemotherapy efficacy [ 79 , 80 , 81 ]. miRNAs can also be detected in CTCs and contribute to a better understanding of the biology and clinical value of these cells [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of ncRNAs can be evaluated in LB at targeted-specific level using amplification-based methods such as reverse transcription quantitative PCR (RT-qPCR) and ddPCR. Of note, the use of ddPCR represents a highly sensitive method to quantify the expression of specific transcripts in LB [ 34 , 35 , 36 ]. In addition, there are other targeted methods such as peptide nucleic acids (PNAs)-based fluorogenic biosensors [ 37 ] and the NanoString nCounter platform that allow for the detection of ncRNA expression levels without the need of previous amplification [ 38 ].…”
Section: Technologies For Epigenetic Assays In Liquid Biopsymentioning
confidence: 99%